Composition of the bio-oil from the hydrothermal liquefaction of duckweed and the influence of the extraction solvents. (1st December 2016) - Yan, Wei-Hong; Duan, Pei-Gao; Wang, Feng; Xu, Yu-Ping
Graphical Abstract: Highlights: Hydrothermal liquefaction of duckweed was performed at 350 °C for 30 min. Effect of extraction solvents on the yields and composition of bio-oils was examined. The polar solvents extracted higher gravimetric yields. Polarity and molecular structure of solvent affect the composition of the bio-oils. Polar solvents provided higher yields and ER of the bio-oils than the nonpolar solvents. Abstract: The influence of the extraction solvents on the yields of the product fractions and on the composition of the bio-oils obtained from the hydrothermal processing of duckweed at 350 °C for 30 min was investigated. Ten solvents were employed including polar solvents (isopropanol, ethyl acetate, dichloromethane, diethyl ether, dichloroethane, benzene, carbon disulfide) and nonpolar solvents (cyclohexane, n -hexane and petroleum ether). The extraction solvents with high relative polarity values tended to produce higher yields of the bio-oils. The highest bio-oil yield of 26 ± 1 wt.% was obtained using isopropanol, followed by dichloromethane (24 ± 1 wt.%). Nonpolar solvents including cyclohexane, n -hexane, and petroleum ether produced the yields of the bio-oils ranging from 3 ± 0.2 to 9 ± 0.4 wt.%. The bio-oils always had a significantly higher C and H contents and a substantially lower O and S contents than those of the biomass material. The C and H contents of the bio-oil from nonpolar solvents, which averaged 78 ± 0.8 wt.% and 10 ± 0.5 wt.%, respectively, were slightly higher than the values from the polar solvents, which averaged 75 wt.% and 9 wt.%, respectively. In contrast, the N and O contents of the bio-oils from nonpolar solvents was lower than that from the polar solvents. The energy recovery (ER) obtained from the polar solvents varied from 42 ± 2 to 60 ± 3%, which is much higher than the ER obtained from the nonpolar solvent (24 ± 1% for cyclohexane) and lowest (10 ± 0.5% for n -hexane). Significant differences in molecular composition were observed in the bio-oils when varying the solvent, and these differences were attributed to the combined effects of the polarity and the molecular structure of each solvent.